2013
DOI: 10.1002/ana.23909
|View full text |Cite
|
Sign up to set email alerts
|

Low Myo‐inositol indicating astrocytic damage in a case series of neuromyelitis optica

Abstract: Astrocytic necrosis is a prominent pathological feature of neuromyelitis optica (NMO) lesions and is clinically relevant. We report 5 NMO-related cases, all with longitudinally extensive lesions in the upper cervical cord, who underwent cervical cord (1) H-magnetic resonance spectroscopy. Lower myo-inositol/creatine values, suggesting astrocytic damage, were consistently found within the NMO lesions when compared with healthy controls and patients with multiple sclerosis (MS), who showed at least 1 demyelinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 14 publications
3
31
1
1
Order By: Relevance
“…In addition, our findings are qualitatively similar to those seen in acute Henning et al, 2008;Ciccarelli et al, 2010) and chronic (Marliani et al, 2010;Ciccarelli et al, 2013) spinal cord lesions in relapsing-remitting multiple sclerosis. The majority of patients with early PPMS included in the present study (n = 12) had a lesion (or part of a lesion) within the spectroscopic voxel and in these patients, spinal tNAA concentrations were lower than patients without a lesion.…”
Section: Differences In Metabolite Concentrations and Q-space Imagingsupporting
confidence: 85%
“…In addition, our findings are qualitatively similar to those seen in acute Henning et al, 2008;Ciccarelli et al, 2010) and chronic (Marliani et al, 2010;Ciccarelli et al, 2013) spinal cord lesions in relapsing-remitting multiple sclerosis. The majority of patients with early PPMS included in the present study (n = 12) had a lesion (or part of a lesion) within the spectroscopic voxel and in these patients, spinal tNAA concentrations were lower than patients without a lesion.…”
Section: Differences In Metabolite Concentrations and Q-space Imagingsupporting
confidence: 85%
“…Although neurons exhibit activity-dependent uptake of myo-Inositol (Uldry et al, 2004), myo-Inositol is more concentrated in glial cells than neurons (Brand et al, 1993;Griffin et al, 2002), and may be critical for glial osmoregulatory functioning (Strange, 1992;Fisher et al, 2002). In neuro-inflammatory conditions, elevated myo-Inositol levels are presumed to reflect astrocyte and microglial activation (Chang et al, 2014, Kirov et al, 2013; conversely, reduced myo-Inositol levels have been interpreted as evidence of astrocyte necrosis in neuromyelitis optica (Ciccarelli et al, 2013). Several postmortem studies have found reduced density of glial cells (Ongür et al, 1998;Hamidi et al, 2004) and decreased concentration of protein markers specific to astrocytes in MDD (MiguelHidalgo et al, 2000;Miguel-Hidalgo et al, 2011;MiguelHidalgo et al, 2014), providing a histological basis for interpreting reduced myo-Inositol levels in MDD as evidence of glial dysfunction (Coupland et al, 2005;Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic parameters quantified by use of 1 H-MRS (eg, ratios of N -acetylaspartate to creatine and choline to creatine, and absolute concentrations of the metabolites) have been reported to be unaltered in the normal-appearing cerebral WM and normal-appearing cerebral gray matter (GM) of patients with NMO spectrum disorder compared with patients with MS. 1820 However, a recent case study of NMO spectrum disorders by Ciccarelli et al 21 demonstrated lower myo -inositol levels normalized to creatine levels in the lesional cervical spinal cords of patients with NMO spectrum disorder in comparison with patients with MS and matched healthy controls. Myo -inositol is a molecule located in astrocytes; low levels of myo -inositol estimated by use of 1 H-MRS are therefore believed to indicate astrocytic damage.…”
Section: Exploration Of Normal-appearing Wm and Normal-appearing Graymentioning
confidence: 98%
“…Myo -inositol is a molecule located in astrocytes; low levels of myo -inositol estimated by use of 1 H-MRS are therefore believed to indicate astrocytic damage. 21 Ciccarelli et al 21 hypothesize that this lesional pathology is distinctive among patients with MS. Nevertheless, this finding needs confirmation by a larger study and preferably also additional data on brain lesions.…”
Section: Exploration Of Normal-appearing Wm and Normal-appearing Graymentioning
confidence: 99%